Perilaku Politik Towani Tolotang di Amparita Kabupaten Sidenreng Rappang - Alfiansyah Alfiansyah; Mahmud Tang; Safriadi Muis (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2018)
This article aims to explain how the political behavior of Towani Tolotang in Amparita of Sidrap Regency in political activities, and how the relationship between Towani Tolotang's political behavior with their belief system. The method used in this research is descriptive research design using qualitative approach. The findings of this study illustrate that the existence of practical political activities in the Tolotang community changed their political behavior and had different views in terms of determining their political choice, The role of Uwa is very influential in the political decision making in Tolotang community, Decision-making also based on the region- certain areas in the Tolotang area based on their respective territories, In essence their decisions are different because of the customary attachment of their leader, Uwa in this case which determines the choice in the Amparita territories, as well as the involvement of Towani Tolotang community in political aspect of one of their efforts in maintaining the customs and beliefs that their ancestors inherited.